Winter segregation and timing of pair formation in Red-breasted Merganser Mergus serrator - Kahlert, Johnny; Coupe, Malcolm; Cooke, Fred (Wildfowl, 1998)
During the late winter and spring of 1997, sex-ratios and pairing chronology of Red-breasted Mergansers were studied in the Fraser River Estuary, south west of Canada. Until late March at one site, English Bay, there was a strong male-bias, whereas a female bias was evident at the nearby Boundary Bay. This pattern was interpreted as sexual winter segregation. At the male- biased site, antagonistic and kleptoparasitic behaviour initiated by males towards females could not account for the winter segregation. In late March and April, the sex ratios at eh two study sites converged to similar values. This trait coincided with an increase in the number of courtship displays and percentage of paired birds. Although the majority of mergansers exhibited this pairing chronology, pairs were observed as early as mid-February, suggesting a gradient in the timing of pair formation. Pairs tended to segregate from flocks. If pairs are able to segregate throughout the winter, early pairing may be beneficial as food resources could be monopolised and interference with conspecifics avoided. However, the frequency of interactions with conspecifics tends to be unpredictable, since local population size fluctuated considerably.